Clinical efficacy of surgery for patients with Chiari malformation type I with syringomyelia: posterior fossa decompression versus posterior fossa decompression with resection of tonsils - Zhang, Lei; Li, Ben Li; Wei, Shuo; Hu, Hong Wei; Chen, Hong Fu; Fan, Yue Chao; Zhang, Hui; Ji, Pei Zhi (Frontiers in Neurology, 2025)
BackgroundThe optimal surgical approach for treating Chiari malformation type I (CM-I) with syringomyelia remains a topic of debate. Key areas of controversy include the extent of decompressive craniectomy, the necessity of subarachnoid exploration, and whether to excise the herniated tonsils. In this study, we present our perspectives on these contentious issues through a retrospective analysis of the clinical efficacy of posterior fossa decompression with resection of tonsils (PFDRT) compared to posterior fossa decompression (PFD).MethodsWe conducted a retrospective analysis of clinical data from 162 patients diagnosed with CM-I and syringomyelia who underwent surgical intervention at the Affiliated Hospital of Xuzhou Medical University between January 2017 and December 2022. Among these, 58 patients underwent PFD, while 104 received PFDRT. The efficacy of the treatments was evaluated using the Chicago Chiari Deformity Prognosis Scale (CCOS) at 6 months post-surgery, with scores ranging from 13 to 16 indicating a favorable prognosis. Furthermore, the improvement of syringomyelia was assessed through magnetic resonance imaging (MRI) at the six-month follow-up.ResultsSix months post-surgery, according to the Chiari Clinical Outcome Scale (CCOS) score, the improved rates for the PFD and PFDRT groups were 56.9 and 78.8%, respectively. Additionally, the recovery rates for syringomyelia in these groups were 55.2 and 76%, respectively. Statistically significant differences were observed in both the rates of favorable prognosis and syringomyelic improvement between the two groups (p < 0.05). The incidence of complications, including fever, cerebrospinal fluid leakage, intracranial infection, and incision infection, did not differ significantly between the groups (p > 0.05).ConclusionOur findings indicate that PFDRT yields superior outcomes in syringomyelia improvement and favorable prognoses compared to PFD, while maintaining comparable postoperative complication rates.